Effective human relations : - Reece, Barry L. (Cengage Learning, 2017)
This comprehensive 13th edition explores goal- setting, the root causes of negative attitudes, the use of "personal branding" and social media in the job market, emotional intelligence, positive psychology and happiness, and how companies create a dynamic company cultures. Self-assessments and self-development opportunities throughout the book teach you to assume responsibility for improving your personal skills and competencies. This text will help you gain the insights, knowledge and relationship skills you need to deal successfully with the wide range of people-related challenges in business today. It is a text you can continue to refer to throughout your life!